A study on factors that affect material costs in semiconductor industry / Amiratul Nadiah Razarudin - Razarudin, Amiratul Nadiah (Faculty of Business and Management, 2011)
Material costs are one of the important costs involved in determining the company’s profit at NXP Semiconductors Seremban Sdn Bhd. Frankly speaking, material costs may give a big impact to the company if the company did not pay attention to the costs, as it can affect production costs, which will lead to the profit. To reduce the rises in material costs, every department involved in determining the material costs should take part and pay fully attention. The company’s objective is to lower the costs, but at the same time increase their profit. And one of the costs that should be reduced is material cost.